2020
DOI: 10.1029/2019rs007004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Positioning Performance Under the Effects of Strong Ionospheric Anomalies With Multi‐GNSS in Hong Kong

Abstract: Global navigation satellite system (GNSS) precise positioning performance will be strongly affected under severe ionospheric anomaly conditions. The combination of multi‐GNSS can increase the available observations and improve the geometry of continuously tracked satellites. This paper focuses on assessing the positioning performance with the combination of Global Positioning System (GPS), Global'naya Navigatsionnaya Sputnikova Sistema (GLONASS), and BeiDou System (BDS) around the St. Patrick's Day geomagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Another study by Lu et al. (2020) have assessed positioning performance with multiGNSS including effects of scintillation events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Lu et al. (2020) have assessed positioning performance with multiGNSS including effects of scintillation events.…”
Section: Discussionmentioning
confidence: 99%
“…However, analyzing data of three CIGALA/CALIBRA network stations in Brazil, precision achieved in kinematic-PPP was reported to be better with integrated GPS and GLONASS data, compared to GPS data alone (Marques et al, 2018). Another study by Lu et al (2020) have assessed positioning performance with multiGNSS including effects of scintillation events.…”
Section: Discussionmentioning
confidence: 99%
“…As the change rate of ionospheric delay is variable with the site and the epoch, it is difficult to precisely model it. Furthermore, the change rate of ionospheric delay is easily influenced by space weather, its value would be very high and most of the ionosphere models also perform badly during high solar activity period [ 31 ]. While for dual-frequency satellite receivers (L1/L2, i.e., 1227.60 MHz), the IF combination can be formed to minimize the ionospheric delay.…”
Section: Time-relative Positioning Algorithm Based On Tdcp Measurementioning
confidence: 99%
“…Although many studies have reported the adverse effects of geomagnetic storm on GNSS, few papers sought ways to mitigate these effects on GNSS precise positioning (Lu et al., 2020; Rodríguez‐Bilbao et al., 2015). Since the number of cycle slip increases in storm conditions, correctly detecting or even repairing cycle slips should be the effective solution to improve GNSS PPP or RTK performance during storm periods.…”
Section: Introductionmentioning
confidence: 99%
“…After that, Lu et al. (2020) reported the multi‐GNSS PPP results during the St. Patrick's Day geomagnetic storm in 2015. Results suggested that, due to the storm effects, both GNSS signal‐to‐noise ratio and multipath observations are changed significantly, and the results of GNSS PPP are systematically deviated.…”
Section: Introductionmentioning
confidence: 99%